An MQTT based Real Time LBS System for Vehicles and Pedestrians - Jung, In-Hwan; Lee, Jae-Moon; Hwang, Kitae (International Journal of Engineering and Technology, 2018)
Background/Objectives: We introduce a real time location based IoT system using MQTT protocol that collects location information of moving devices and provides messaging service between based on administrative area unit.Methods: We implemented an MQTT based a smartphone application for pedestrian location information service and a Raspberrypi IoT device for vehicle information processing and messaging. IoT clients can send messages to the server according to administrative area units by publishing data to an MQTT topic, which is equal to administrative area names. We also implemented an LBS data server and LBS application server for location based data analysis and messaging service.Findings: The SLIMS (Seoul Location based IoT Messaging System) implemented in this research is able to analyze the real time traffic statistics of pedestrians and vehicles. It also can deliver messages to clients based on coordinate range and administrative area units. SLIMS is implemented for Seoul city but can be applied to any part of the country if map data that distinguish administrative districts is replaced. In addition, it is designed and implemented so that any IoT devices with GPS sensors can be applied even though it is currently implemented for smart phones and automotive devices.Applications: The SLIMS can be used as a real-time location-based information service for large-scale IoT devices such as real-time pedestrian population and vehicle traffic analysis and location-based message delivery.Â Â